Groundwater: a juggernaut of socio-economic development and stability in the arid region of Kachchh - Patel, Praharsh M.; Saha, D. (Informa UK Limited, 2022)
Kachchh, the westernmost district of India is historically known for its unique landscape, distinct traditions and arid climate. For a long time, the arid region of Kachchh had limited economic growth and limited habitation due to water scarcity caused by erratic rainfall. In 2001, the seismically active region of Kachchh experienced a large earthquake measuring 7.7 Mw but, the region has shown considerable development post-disaster. Growth strategies for agriculture, manufacturing and tourism implemented by the government and supported by industries and other agencies have not only made the region a dynamic economic hub in the state of Gujarat, but also has highlighted the long-neglected region on the world map. Due to the lack of perennial surface water availability and limited rainfall, the development has been fuelled by exploiting the groundwater resources to a great extent. The objective of this chapter is to highlight groundwater use in Kachchh, known as one of the most arid regions of India with low rainfall and high variability. Groundwater is playing a vital role in meeting the demand for all societal usage, irrigation, domestic requirements and industries. The authors highlight how the region is blessed with a suitable geological formation, forming a potential freshwater aquifer system which has served society for centuries even with a grossly adequate recharge. They highlight the importance of looking into the sustainable use of groundwater, a priceless natural resource of the region.